Hotel and Restaurant Tax Contribution Analysis to Local Income in Tegal District from 2016 to 2020: ANALISIS EFEKTIVITAS, EFISIENSI DAN KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN TEGAL TAHUN 2016-2020 - Wardana, Linda Kusumastuti; Kurniawati, Cici (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2022)
One of the important aspects of the company is performance measurement. This performance measurement can be used to determine the success of the company and build the foundation for award design within the company. Balanced Scorecard is a term that aims to balance financial and non- financial aspects. The purpose of this study is to determine the performance of PT Sariguna Primatirta Tbk when measured by the Balanced Scorecard. This study uses the Balanced Scorecard to evaluate the performance of PT Sariguna Primatirta Tbk using the Balanced Scorecard of the proposed research. The method used is quantitative by using secondary data in the form of an overview, company documents. The results of this study indicate that the company's performance measurement using the Balanced Scorecard has been carried out, the performance score of PT Sariguna Primatirta Tbk shows that the company's performance is in a "good" condition and the achievement of management is quite optimal in accordance with the provisions set by the company.